The Correlation among Reading Motivation, Reading Anxiety, and Reading Comprehension of Tenth-Grade Students in Palembang - Sabrina, Alra; Astrid, Annisa; Desvitasari, Deta (Acitya: Journal of Teaching and Education, 2025)
This study examined the correlation among reading motivation, reading anxiety, and reading comprehension of tenth-grade students in Palembang. A quantitative correlational research design was employed, involving 509 students from SMA Bina Warga 1 Palembang and SMA Negeri 15 Palembang. Using cluster random sampling, 107 students were selected as the sample. Data were collected through a reading comprehension test and two questionnaires measuring reading motivation and reading anxiety. The findings indicated no significant correlation between reading motivation and reading comprehension (r = 0.087, p = 0.375), indicating that motivation to read did not influence students’ understanding of texts. Likewise, no notable correlation was identified between reading anxiety and reading comprehension (r = -0.022, p = 0.824), suggesting that anxiety was not a determining factor. These results revealed that reading motivation and reading anxiety did not have a substantial effect on reading comprehension. This suggests that psychological factors such as motivation and anxiety alone may not serve a decisive role in shaping reading comprehension. Instead, other factors such as teaching methods, students’ backgrounds, individual skills, and the learning environment may contribute to reading comprehension outcomes. The study offers insights for English teachers in designing reading instruction that considers multiple influencing factors. It may also guide future researchers in exploring additional variables affecting reading comprehension.